The Role of Digital Media and Peer Influence on Adolescent Smoking Behavior: A Critical Analysis of Intervention Strategies - Chaudhary, Neha; Jatal, Manika (NPRC Journal of Multidisciplinary Research, 2024)
This study is an attempt to explore perceptions and attitudes toward smoking amongst adolescents, where the main objective of the research is to explore the factors that help in understanding how their views and behavior are shaped. This study garnered data through questionnaires given to adolescents between the ages of 10-20, representing varied walks of life. The results bring out intricate interplays of social, psychological, and environmental factors that shape adolescent perceptions. Peer pressure, media representation, and familial attitudes emerge as potent determinant factors. The research therefore stresses the implementation of focused educational programs and policies aimed at dispelling myths in order to reduce smoking initiation rates during this period. Recommendations for further research and intervention are discussed here, which would form the foundation of comprehensive anti-smoking strategies relevant for this most vulnerable age group.